Legal Assistance of Government Law Office in the Procurement of Goods and Services - Susilo, Susilo; Utama, Muhamad Adji Rahardian; Rajagukguk, Anita Carolina (Faculty of Law Universitas Negeri Semarang, 2021)
Procurement of goods/services is an activity to obtain goods/services by other Ministries/Institutions/Regional Work Units/Institutions whose process starts from planning needs to completion of all activities to obtain goods/services. The goods/service procurement activities are financed by the APBN/APBD, either carried out independently or by goods/service providers. The procurement of goods/services is essentially an attempt by the user to obtain or realize the goods/services it needs, by using certain methods and processes in order to reach an agreement on specifications, prices, time, and other agreements. The President of the Republic of Indonesia, in the process of dealing with the Covid-19 pandemic, has given instructions that were forwarded to the Deputy Attorney General for Civil and State Administration through circular number SE-02/G/Gs.2/04/2020 to carry out the stages quickly, precisely, focus integrated and synergistic among Ministries, institutions and local governments in the process of procuring goods and services. In the procurement process in an emergency, there are at least four important phases, namely planning, implementing, settling payments, and auditing. One of the duties and functions of the Junior Attorney General for Civil and State Administration is Legal Considerations consisting of Legal Opinion, Legal Assistance, and Legal Audit. Legal Assistance is a legal service provided by the State Attorney in the form of a legal opinion on an ongoing basis on an activity proposed by the Petitioner and ends with a conclusion on the provision of such Legal Opinion in the form of Legal Assistance Official Report.